Macroeconomic policy and unemployment by economic activity: evidence from Turkey - Hakan Berument; Nukhet Dogan; Aysit Tansel (Institute for the Study of Labor (IZA), 2008)
This paper investigates how macroeconomic policy shocks in Turkey affect the total unemployment and provides evidence on the differential responses of the unemployment by sectors of economic activity. Our paper extends the previous work in two respects. First, we consider not only the response of total unemployment but also the response of unemployment by sectors of economic activity. Second, we consider not only the effect of monetary policy shocks, but also the effects of several other macroeconomic shocks. The quarterly data used which covers the period 1988:01 to 2004:04 from Turkey. A VAR model with a recursive order is employed to estimate the effects of shocks in real GDP, price, exchange rate, interbank interest rate, money supply and own sectoral unemployment on unemployment by sectors of economic activity. The results indicate that the positive income shock is followed by a decrease in unemployment in all economic activity groups during the initial periods except the unemployment in the Electricity sector and the Community Services sector. A positive money shock decreases unemployment in sectors of Mining, Manufacturing, Construction, Wholesale-Retail Trade, Transportation and, Finance-Insurance. Opposite results are obtained with the interbank interest rate shocks. Even if, they are not statistically significant, a positive interbank interest rate shock increases the unemployment in all economic activities at the initial levels but derives down the unemployment in the Agriculture and the Community Services sectors at the initial level. Moreover, a positive price shock increases unemployment in all economic sectors in the long run except the Mining and the Community Services. Thus, unemployment in different sectors of economic activity responds differently to various macroeconomic policy shocks.
urn:nbn:de:101:1-20080421187
Keywords: E60; 330; Macroeconomic policy shocks; unemployment by economic activity; Wirtschaftspolitik; Schock; Arbeitslosigkeit; Branche; Wirkungsanalyse; Schätzung; Türkei